Effect Of Concentration Of Papaya Leaf Filtrate (Carica Papaya L.) And Citric Acid On Quality Of Goat’s Milk Dangke - Ernestine, C.V; Rosida R; Jariyah (Food Science and Technology Journal (Foodscitech), 2021)
Dangke is a dairy product that is shaped like cheese from Enrekang (South Sulawesi) which is made by coagulating milk with papain. The use of papaya leaf filtrate causes bitter taste in dangke, the addition of citric acid as coagulant combination can control the proteolytic activity and covers an unfavorable after taste. This study aims to determine the effect of the concentration of papaya leaf filtrate and citric acid on the physicochemical and organoleptic characteristics of goat's milk dangke. This study used a factorial completely randomized design (CRD) with two factors, factor I was the concentration of papaya leaf filtrate (0.5%, 1%, 1.5%) and factor II was the concentration of citric acid (0.5%, 1 %, 1.5%). The data obtained were analyzed using ANOVA and if there was a significant difference between treatments, it was continued with the DMRT follow-up test at 5% level. This study showed a significant interaction between papaya leaf filtrate and citric acid on yield, water content, fat content, texture score, color score and taste score. Dangke goat's milk with papaya leaf filtrate concentration of 1.5% and citric acid concentration of 0.5% is the best treatment with yield characteristics 10,6%; water content 54,47%; ash content 2,14%; protein content 21,25%; fat content 13,05% and pH 4,89 and hedonic score of texture 4,60 (slightly soft), aroma 3,30 (smells typical of goat's milk), color 2,25 (not very white), and taste 3,00 (bitter).